Aptness Predicts Metaphor Preference in the Lab and on the Internet. (2nd January 2016) - Roncero, Carlos; de Almeida, Roberto G.; Martin, Deborah C.; de Caro, Marco
ABSTRACT: Experimental studies have suggested that variables such as aptness (Chiappe & Kennedy, 2001) or conventionality (Gentner & Bowdle, 2008) are predictors of people's preference for expressing a particular topic–vehicle pair (e.g., "time–money") as either a metaphor ("TIME IS MONEY") or a simile ("TIME IS LIKE MONEY"). In the present study, we investigated if such variables would also be predictive within a more naturalistic context, where other variables, such as the intention to include an explanation (Roncero, Kennedy, & Smyth, 2006), may also influence people's decision. Specifically, we investigated the production of metaphor and simile expressions on the Internet via the Google search engine and checked for accompanying explanations, as well as the properties they expressed, to examine whether ratings such as aptness, conventionality, as well as participants' own stated preference or the intention to produce an explanation, would predict which topic–vehicle pairs appeared more often as metaphors. We found that participants' stated preference predicted metaphor dominance on the Internet, and that apt topic–vehicles occurred more often as metaphors. The explanations collected, however, occurred 82% of the time after similes, and familiar expressions were the most explained. Finally, comparing the properties expressed in these explanations to normed property lists, we found that simile explanations typically expressed a novel conception of the topic–vehicle relationship. Therefore, we found that Internet posters use metaphors to convey an apt relationship, as found in previous laboratory studies, but prefer using a simile frame when they want to express a relationship that readers will find novel.